A BEST example of channel structure annotation by molecular simulation - Rao, S; Klesse, G; Stansfeld, P; Tucker, S; Sansom, M (Taylor and Francis, 2017)
An increasing number of ion channel structures are being determined. This generates a need for computational tools to enable functional annotation of channel structures. However, a number of studies of ion channel and model pores have indicated that the physical dimensions of a pore are not always a reliable indicator of its conductive status. This is due to the unusual behavior of water within nano-confined spaces, resulting in a phenomenon referred to as ‘hydrophobic gating’. We have recently demonstrated how simulating the behavior of water within an ion channel pore can be used to predict its conductive status. In this addendum to our study, we apply this method to compare the recently solved structure of a mutant of the bestrophin chloride channel BEST1 with that of the wild-type channel. Our results support the hypothesis of a hydrophobic gate within the narrow neck of BEST1. This provides further validation that this simulation approach provides the basis for an accurate and computationally efficient tool for the functional annotation of ion channel structures.